Atrioventricular nodal ablation and implantation of mode switching dual chamber pacemakers: effective treatment for drug refractory paroxysmal atrial fibrillation. Issue 6 (1st June 1998) - Marshall, H J; Harris, Z I; Griffith, M J; Gammage, M D
Abstract : Objective: To assess the effect of atrioventricular node ablation and implantation of a dual chamber, mode switching pacemaker on quality of life, exercise capacity, and left ventricular systolic function in patients with drug refractory paroxysmal atrial fibrillation. Patients: 18 consecutive patients with drug refractory paroxysmal atrial fibrillation. Methods: Quality of life was assessed before and after the procedure using the psychological general wellbeing index (PGWB), the McMaster health index (MHI), and a visual analogue scale for cardiac symptoms. Nine of the patients also underwent symptom limited exercise tests and echocardiography to assess left ventricular systolic function. Results: The procedure allowed a reduction in antiarrhythmic drug treatment (p < 0.01). PGWB and symptom scores improved (p < 0.01) but the MHI score did not change. Left ventricular systolic function and exercise capacity were unchanged. Conclusions: Atrioventricular node ablation and implantation of a DDDR/MS pacemaker is effective treatment for refractory paroxysmal atrial fibrillation, producing improved quality of life while allowing a reduction in drug burden. The popularity of the treatment is justified, but further studies are needed to determine optimum timing of intervention.